Breaking through the Ivory Tower of High-Indexed Journals: ‎ Insights from EFL Academics in East Java, Indonesia: - Tajuddin, Azza Jauhar Ahmad; Fadhilawati, Dian; Risdianto, Faizal; Suyitno,; Supriyono,; Saifudin, Ahmad (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to assess the productivity levels and challenges EFL academics face at private universities in East Java when publishing research in Scopus and Web of Science (WOS)-indexed journals and propose strategies for improving publication success. Methods: The study used a sequential explanatory mixed-methods design. A preliminary analysis of 288 EFL academics' publications indexed in Scopus and WoS was conducted using data from the Sinta database to evaluate productivity levels. To identify the main barriers to publishing in high-impact journals, an online survey was administered to 167 targeted EFL academics, with 165 completing it. Six participants were then interviewed in depth to gain further insights. Results: The study indicates low research productivity among EFL academics in Scopus and WoS-indexed journals publications. The main barriers included financial constraints (high APCs, limited institutional funding), research competence (insufficient writing skills, difficulty publishing in reputable free journals, limited technology/AI proficiency), and institutional support/mentorship (lack of guidance, restricted access to resources, insufficient mentorship programs, and absence of personal mentors). Conclusions: The findings highlight the urgent need for financial support, targeted academic writing training, investment in technology and artificial intelligence tools, and credible resource subscriptions. Academic mentorship from experts is also essential to strengthening EFL academics’ capacity to publish in high-impact international journals.